BAHASA DAN IDENTITAS: POLA SALAM DOSEN DALAM INTERAKSI VERBAL DI LINGKUNGAN KAMPUS MULTIKULTURAL - Puspita Dian Agustin; Sitti Rachmi Masie; Nuramila Nuramila (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2026)
This paper describes the greeting patterns that arise and are used by the campus community of Gorontalo State University, especially lecturers with a multicultural basis. The scope of the discussion is limited to the pattern of use of greeting words when interacting in the work environment with social constraints in the activity of selecting the type of greeting word that is in accordance with social identity and its variants. As a comparison, the Ervin-Tripp model (1969) is used, which analyzes greeting patterns in American English. The results of the comparison show that in English the greeting pattern is dominated by personal names and seven choices of greeting forms. Meanwhile, in Indonesian (in Gorontalo) the pattern of use of greeting words is dominated by kinship terms with eleven main patterns and a number of choices of greeting forms. Each use of greeting words spoken by each lecturer in the campus environment forms a personal identity directly to classify language speakers and their language.